Keynote Paper : Financial Vulnerability Among Malaysians Amid Covid19 - Nuradli Ridzwan Shah Mohd Dali; Wan Rasyidah Wan Nawang; Hanifah Abdul Hamid; Umi Hamidaton Mohd Soffian Lee; Wan Nur Fazni Wan Mohamad Nazarie (Universiti Sains Islam Malaysia, 2024)
Keynote Paper